Regulation of pro-metastatic Notch3 receptor in melanoma - Monto, Elisa (My University, 2023)
Metastatic melanoma, which can form distant metastases through the lymphatic vessels, is the deadliest type of all skin cancer. Lymphatic endothelial cells facilitate metastasis of melanoma cells by activating the Notch3 signaling pathway in melanoma cells upon contact. The Notch signaling pathway regulates various fundamental functions of the cells, but overactivity of the pathway is associated with many cancers. However, it is not exactly known which Notch ligands can activate Notch3 receptors in melanoma cells. Notch3 signaling can be regulated in different ways. PIM kinases are known to affect Notch3 signaling in breast and prostate cancer cells in a tumorigenic manner, but it is not known whether PIM kinases can contribute to the regulation of Notch3 signaling in melanoma cells. The aim of this thesis was to examine how Notch3 signaling is regulated in melanoma cells. Melanoma cells were treated with immobilized Notch ligands fused with a Fc-fragment to address which Notch ligands activate Notch3 signaling. In addition, cells were treated with siRNAs targeting PIM 1 3 kinases to investigate whether PIM kinases contribute to the regulation of Notch3 signaling in melanoma cells. The activity of Notch3 signaling was determined by analyzing the mRNA and protein levels of its downstream targets, and the invasiveness of cells induced by Notch3 activation was examined using a 3D invasion assay. This study provided evidence that especially Notch ligands DLL4 and DLL1 can activate the tumorigenic Notch3 signaling in melanoma cells. Moreover, DLL4 treatment also promoted the invasion of metastatic melanoma cells in 3D fibrin, whereas the invasion of non-metastatic melanoma cells was not induced. Furthermore, PIM2 appeared to have a potentially oncogenic role in melanoma cells, since DLL4-mediated invasiveness of melanoma cells was reduced upon PIM2 silencing.
Keywords: Melanoma, Notch signaling, Notch3, PIM kinases, Delta-like ligand 4 (DLL4), Delta-like ligand 1 (DLL1)